Linguistic and Cultural Aspect of Interpretation of Aphoristic Expressions with Zoocomponents ‘Dog’ and ‘Horse’ (Khanty and Khakass Languages) - A. D. Kaksin (Научный диалог, 2022)
The article is devoted to one of the aspects of the linguistic substantiation of the connection between language and culture: the identification of lexical units with a potential conceptual meaning in thematic groups, which allows them to participate in the creation of aphoristic idioms (aphorisms, proverbs, sayings). From the standpoint of linguistic typology in the lexico-semantic sphere, the words denoting a dog and a horse in the Khanty and Khakass languages are considered. The empirical base of the study was the author’s notes of the spoken language of the Khanty, dictionaries of the Khanty and Khakass languages, a collection of Khanty riddles, a collection of Khakass proverbs and sayings. As a result of the study, a circle of idioms (indicated languages) with a distinct cognitive and mental, worldview basis is outlined. The methods used are the method of typological interpretation of lexical material and descriptive. When analyzing the semantics of these words, special attention was paid to the indication of regular stable phrases: it is the associative potencies that are the basis for the development of further connotations, the logical conclusion of which is the participation of certain words in idioms. It has been established that idiomatic constructions with the lexemes ‘dog’ and ‘horse’ characterize not so much these animals as the way of life of two different ethnic groups, as well as the human qualities of the representatives of these peoples, shed light on their ideas about life.